Application of A PEEC Method in Backflashover Simulation of HV Transmission Lines in Thailand - Yutthagowith, P.; Sirachansawang, P. (My University, 2019)
For high voltage transmission lines, direct lightning strikes a tower shielding wire can cause the backflashover phenomena. In this paper, the partial element equivalent circuit (PEEC) method was used as a simulation tool for study of these phenomena of typical 230-kV transmission lines. The discharge process on string insulators is represented by the disruptive effect (DE) method. The lightning current ranges with various tower grounding impedances, causing backflashover in the 230 kV double circuit line with two grounded shielding wires have been investigated in detail. Preventing 95% of lightning strikes causing the backflashover, the proper grounding impedance can be determined.
Keywords: backflashover; direct lightning strike; tower grounding impedance; transmission lines.